Study Of The Structure Of An Optoelectronic Device Designed For Product Quality Control (Eurasian Research Bulletin, 2022)
In clause is considered gas the analyzer on a basis optical electronic two-wave generator in which through the gas chamber is used optical feedback. At on an output of the generator a positive pulse the optical feedback on length to a wave l1 is provided and at negative - l2 .